Literature Review: Optimizing Human Resource Development to Improve the Quality of Police Performance through a Talent Scouting Strategy - Nur Cahyo Ari Prasetyo; Riska Sri Handayani; Chairul Muriman Setyabudi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
According to a survey by the Indonesian Political Indicator Survey Institute, public trust in the National Police decreased from 79.8% in 2019 to 72% in 2020. Despite this decline, data from Puslitbang Polri suggests that public trust is expected to increase from 69.35% in 2022 to 76.40% in 2023. This study aims to improve Polri performance by optimizing human resource development and implementing talent scouting strategies. The research method used is a qualitative method with a literature review approach. The results show that efforts need to be made to optimise the development of Polri human resources towards Polri performance, namely big data development by developing the SIPP application, talent management police by looking for Polri talents in the field of intelligence, technology development by developing a supervisory system through microlearning learning, and job design is needed as a mapping of each task force. The results of the implementation of talent scouting strategies to improve the quality of Polri performance on Polri personnel are carried out by developing interests and talents in the field of intelligence in order to achieve precision Polri. Thus, it can be concluded that the development of Polri human resources is able to have a positive influence on Polri performance, so that public trust in Polri performance is increasing. In addition, Polri's performance has increased significantly and has been running well, so that Baintelkam Polri is able to obtain talented officers because they have good expertise and quality in the field of intelligence.